The Determining Aspects of Vocational High School Students' Career Choice: A Phenomenological Study in Industrial Areas - Sayuti, Muhammad; Kunta Biddinika, Muhammad; Hasanah, Noviatun; Agus Susanto, Harry; Aristi Utami, Dyan; Handayani, Tri; Suyanto, Sigit (IJORER : International Journal of Recent Educational Research, 2026)
Objective: The high unemployment rate of vocational high school graduates (9.01%) contrasts with the availability of jobs in industrial areas, indicating a gap between competency and career choices. This study aims to examine the determinants of career choices of vocational high school students in industrial areas through a phenomenological approach. Method: This phenomenological study involved five 12th-grade vocational high school students in the Weleri-Kendal industrial area using semi-structured interviews. Results: The results show that career choices are determined by a dynamic interaction between personal factors (intrinsic interest), the view of success as an internal factor, entrepreneurial spirit as an adaptive strategy, and responses to economic and social realities. Field Work Practice (PKL) experiences play a central role in career validation. Entrepreneurial spirit functions as an adaptive strategy that helps students overcome uncertainty. These findings imply the need for transformation of career guidance services in vocational high schools from merely providing job vacancy information to facilitators that build students' self-efficacy, tolerance for uncertainty, and adaptive capacity through a holistic approach. Novelty: The novelty of this research lies in deepening the meaning of students' lived experiences amidst the pressures of the industrial ecosystem, which has so far been neglected in survey-based research to understand the dynamics of career choices of vocational high school students in developing countries.